Impacts of crop residues on soil health: a review. Issue 1 (1st January 2021) - Fu, Bin; Chen, Ling; Huang, Hongying; Qu, Ping; Wei, Zhenggui
ABSTRACT: Crop residues are mainly post-harvest remains of agriculture. The organic matters, nutrients, and hollow structures of crop residues enable them to be applied in agriculture. In this review, we summarize the impacts of crop residues on soil health. Crop residue returning is beneficial to soil physicochemical properties. Soil water content, total porosity, aggregate stability, cation exchange capability (CEC), organic carbon, phosphorus, and potassium all increased after being amended with crop residues. The negative effects of allelochemicals from crop residues on crop growth can be adjusted by crop residue returning management. The rice straw has positive impacts on soil microbial properties. Besides, crop residue play a crucial part in soil remediation. Crop residues as soil amendments have inhibitory effects on some heavy metals, organic pollutants, and pathogens. They can also alleviate the pressure of saline-alkali soil. Finally, we provide some suggestions for improving soil health with crop residues.